Co-digestion, pretreatment and digester design for enhanced methanogenesis. (February 2015) - Shah, Fayyaz Ali; Mahmood, Qaisar; Rashid, Naim; Pervez, Arshid; Raja, Iftikhar Ahmad; Shah, Mohammad Maroof
Abstract: Co-digestion, pretreatment and digester design are the key techniques for enhanced biogas optimization. Co-digestion dilutes the inhibitory effects of substrates, balance the micro and macronutrients, increase the organic loading with consequent higher methane yields per unit of digester volume; lastly diversify and synergize the microbial communities which play pivotal role in the methanogenesis. Pretreatment facilitates in conversion of polymers to monomers and increased accessibility of the food to microbes. Proper and accessible feed have a crucial role in the biogas enhancement. The biodegradability of any particular biomass depends on its source from which it has been derived. The biodegradability of a biomass may be affected by various factors like crystalline structure the extent of cellulosic polymers; the surface properties of biomass, the amount of lignin content, the presence of hemicellulosic materials and the strength of fibers. The present review also discussed various types of the pretreatment to remove the obstacles before feeding for biogas digesters. Various biomasses being utilized for the anaerobic digestion of biogas optimization were discussed. The current review also discussed the digester design along various operation physical conditions and the nature of feed substrates employed for biogas optimization.